Seismic Analysis and Design of Residential Building Based on Indonesian Code - Syahrum, Samsul (2007)
Located in active earthquake zone, all buildings in Indonesia should be designed to follow strict building code requirements to be able to resist designated earthquake load. The earthquake loading as a lateral loading should be taken into account in the analysis of a residential building, especially for places in high seismic zones. The analysis and design will be analyzed using SAN’S software. The static equivalent lateral forces analysis based on the Indonesia seismic code procedure will be used to estimate the seismic loading. The earthquake loading produced will be applied to the actual building in Pekanbaru – Riau – Indonesia for 1,2,3,and 4 storey .